Improving the Role of Experts under Indonesian Criminal Procedure Law: Lessons Learned From the Dutch Legal System - Sitompul, Josua (UI Scholars Hub, 2018)
This article attempts to scrutinize the role of expert under KUHAP and examine how Indonesian courts have interpreted and applied relevant rules and principles of the expert in selected cybercrime cases. It finds that the main role of expert in such cases is providing the courts with opinions on the legal and technical meanings of the legal provisions at stake and their contextualization in the cases. This raises a question whether law enforcement agencies comprehend the execution of the provisions. It also shows that law enforcement agencies are not always interested in getting digital forensic examination from which electronic evidence may be produced. It emphasizes that role of expert under KUHAP is equivocal and views the need to improve the role and principles. In order to improve the role of experts under Indonesian criminal law, the article describes and explains the salient features of expert evidence under Dutch law. The article concludes by making a series of recommendations.